PEMBENTUKAN WARGA NEGARA DEMOKRATIS DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - ., Samsuri (PKn Progresif, 2006)
This paper describes building of citizen?s characters through the citizenship education. It attempts to trace the conceptualization of civic education in Indonesia and its main problem within old paradigm. The new civic education paradigm has reliability with universal concepts on citizenship in democracy. For it, the paper explained the some concepts on the core of citizenship education which be formulated by the experts of citizenship education at the world. The models of civic learning and the urgency of the professional?s civics teachers are importance topics to create democratic citizenship.